FAKTOR - FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN DISFUNGSI SEKSUAL PADA WANITA MENOPAUSE DI WILAYAH KERJA PUSKESMAS PATUMBAK - Khairani Khairani (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2022)
Sexual dysfunction is a decrease of libido or sexual desire in a person within sexual intercourse due to biological problems, psychological, and interpersonal factors. Sexual dysfunction often happens in household life, if sexual dysfunction often occurs in household life, if it is not promptly treated, it can lead to crack the household. One of the factors can cause the cracks in the household life, it is approximately 12% due to the problems of sex. While sexual problems that experienced by husbands and wives of more than 66%. This is because many couples are not disputed or it is able to mute, so it does not need get into fuss. This research aimed at identifying and describing the incidence of sexual dysfunction and the dominant factor affecting the incidence of sexual dysfunction in menopausal women. The approach of this research employed quantitative approach using cross sectional design. The population is 198 menopausal women and have spouses. The samples are 76 respondents using proportional random sampling technique. The data collection technique in this research used the direct interview FSFI questionnaires through home visits and conducted measurements of height using stadio meter and weight using digital scales. Statistical test in this research used Chi Square test and Multiple Logistic Regression. The results of this research showed that all variables are related to the incidence of sexual dysfunction, and the dominant variable is lenght of menopause, determined by OR = 28. This study suggests to increase service about sexual dysfunction upon the menopausal spouse that are related to the history of systematic diseasesÂ by facilitating the respondents to consult with experts who concern with sexual dysfunction, because many menopausal women are still not aware of the information about sexual dysfunction.